Religion, Politics and Law in 19th Century Latin America - Di Stefano, Roberto Daniel (2010)
When revolutions for independence broke out, religious life in the Spanish American world was ruled by the Indian patronage regime [patronato], which gave the monarch tight control over ecclesiastical institutions. Patronage included, among many other prerogatives, presenting candidates to the pope, appointing parish priests and doctrine teachers, the right to allow or deny the dissemination of council and pontifical documents (exequatur), and controlling tithes. The right to patronage had multiple origins: the initial pontifical concession, support for the churches, and its alleged inherence in sovereignty. In the 18th century, however, the idea that patronage was an attribute of the sovereign in its own right had become an almost indisputable opinion.